MOLECULAR CHARACTERIZATION OF COLD TOLERANT GERMPLASM OF PHASEOLUS BEANS WITH SEQUENCE RELATED AMPLIFIED POLYMORPHISM (SRAP) AND RETROTRANSPOSON-BASED INTERPRIMER BINDING SITES (iPBS) MARKERS - B.T. Certel; H. İkten; Y. Yilmaz; F. Kantar; V. Çiftçi; V. Gözen; A. Tepe (Journal of Animal and Plant Sciences, 2023)
In this study genetic diversity of 55 Phaseolus sp. beans selected for cold tolerance from different regions of Türkiye was investigated by using sequence related amplified polymorphism (SRAP) and retrotransposon-based interprimer binding sites (iPBS)markers.. Four commercially registered cultivars, one accession of Phaseolus coccineus and a tepary bean Phaseaolus acutifolius species were included for comparison. Genomic DNA was isolated from young fresh leaves and PCR reaction was carried out using 30 SRAP (sequence related amplified polymorphism) and 12iPBS (retrotransposon-based interprimer binding sites) primers. Similarity analyses were performed and dendrograms were produced according to the Unweighted Pair-Group Mean Arithmetic method (UPGMA). In PCR reactions, 331 total and 146 polymorphic bands were produced with 30 SRAP primer combinations. The number of polymorphic bands ranged between 1 and 12 with an average 4.86 polymorphic marker for each primer pair. Twelve iPBS primers produced 156 total bands and 72 of them were polymorphic. The highest polymorphism was obtained with SRAP primer combinations of Me8Em3 and Me7Em14 and iPBS primers 2270,2394 and 2252. Characterization of germplasm with SRAP and iPBS primers was discussed in relation to cold tolerance, species, source, seed size, seed color and growth type. In conclusion, genetic variability of germplasm of 55 Phaseolus bean species, genotypes and cultivars selected for cold tolerance were effectively assessed by PCR based molecular techniques, SRAP and iPBS. High levels of polymorphism determined in the core collection may be used in breeding programs for the development of cold tolerant superior cultivars.
Keywords: Phaseolus sp. Beans; Chilling Tolerance; Landraces; Genetic Diversity